IMPLEMENTASI PROGRAM SUSTAINABLE DEVELOPMENT GOAL DESA DI DESA POGUNGKALANGAN KECAMATAN BAYAN KABUPATEN PURWOREJO - Ma’rufah, Sholikhatun; Kusmarianto, Cicuk (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This research aims to determine the implementation of the Village Sustainable Development Goals (SDGs). SDGs program and find out the obstacles in implementing the Village SDGs program in Pogungkalangan Village, Bayan District, Purworejo Regency. The method used is descriptive qualitative. Data sources were obtained from observation, interviews and documentation. The technique for determining informants uses the purposive sampling method. Data analysis techniques go through the stages of data collection, data reduction, data display, and drawing conclusions. Researchers use the theory put forward by Ripley and Franklin in Winarno (2007:145), namely: (1) level of compliance; (2) smooth routine; (3) implementation and impact. The results of this research are that the implementation of the  SDGs program in Pogungkalangan Village is not going well and there are several obstacles. The obstacles found were the Village SDGs working group which lacked discipline in carrying out its duties, the village government which neglected to update Village SDGs data, the community's lack of knowledge regarding procedures for providing input to basic Village SDGs data, and the Village SDGs web server which frequently experienced errors.